THE IMPACT OF WORKING CAPITAL MANAGEMENT TO PROFITABILITY OF MANUFACTURING COMPANY LISTED IN INDONESIAN STOCK EXCHANGE - Valiensi Utia; Nanny Dewi; H. Sutisna (Hasanuddin Economics and Business Review, 2018)
ABSTRACTÂ Manufacturing companies in Indonesia are increasing in number in recent years. Large growth should be balanced with good working capital management due to the manufacturing company is carrying out buying of raw material activity, afterward convert them into semi-finished goods and finished goods. Cycles from purchasing goods, inventory management, debt repayment, product sales, cash received will have effect on profitability.Purpose of this study to determine whether working capital management affect profitability of manufacturing companies publicly listed on Indonesian Stock Exchange from 2010-2015. This study uses quantitative method by using linear regression analysis tool on panel data.Results of this study found that the component of working capital proved to affect profitability of manufacturing companies Listed in Indonesian Stock Exchange. Therefore the companies should be able to manage properly their working capital. Manufacturing companies should improve their management pattern applied to their current assets and current liabilities. Working capital management should be performed by shortening cash conversion cycle, debt withholding, and by increasing current assets value due to it proves to be able to improve profitability of the company.